FORMULA PASTA DAN TEH DAUN GEDI MERAH (Abelmoschus manihot L.) SEBAGAI BAHAN TERAPI ALTERNATIF KOMPLEMENTER PERUBAHAN PROFIL LIPIDA PADA KASUS DISLIPIDEMIA (STUDI LABORATORIUM) - Supriyadi Supriyadi; Onny Setiani; Mardiyono Mardiyono (JURNAL LITBANG PROVINSI JAWA TENGAH, 2016)
Dyslipidemia is a risk factor for cardiovascular disease is the leading cause of death in the world and in Indonesia. Treatment in some patients experience side effects include nausea, vomiting, headache, muscle pain and flatulence necessitating alternative or complementary medicine. Red gedi leaf is one of the medicinal plants which contain tannins, polyphenols and flavonoids were allegedly able to affect the lipid profile (cholesterol, triglycerides, LDL and HDL). This study aims to determine the effectiveness of red-leaf gedi (Abelmoschus manihot L.) in the form of pasta and tea with the content measured against changes in lipid profile rat (Rattus novergicus) hyperlipidemia, so it can be used as an alternative or complementary medicine in cases of dyslipidemia. The study was quantitative with true experimental method. Design or study design is randomized two groups and one positive control pretest-posttest design. Subject of research that 18 rats (Rattus novergicus) male wistar strain were divided into three groups: those fed atherogenic simvastatin and simvastatin 0.10 mg, the group given feed atherogenic pasta and red gedi leaves pasta 128 mg containing 100 mg of flavonoids , as well as the group given feed atherogenic tea and red gedi leaves tea 4.5 g containing 100 mg of flavonoids for 7 days. Lipid profile checked by CHOD-PAP method. Data were analyzed using paired t test, ANOVA and post hoc repeated. Decreased levels of cholesterol with simvastatin (41.81%) were significantly (p = 0.000) and better than the pasta (11.60%; p = 0.011) and tea (7.37%; p = 0.005). Decreased levels of triglycerides and simvastatin (41.82%) were significantly (p = 0.023) and equally well with pasta (38.09%; p = 0.006) but better than tea (14.22%; p = 0.358). Decrease in LDL cholesterol with simvastatin (80.99%) were significantly (p = 0.000) and at better than pasta (56.79%; p = 0.001) but better than tea (0.41%; p = 0.945). Increased levels of HDL using simvastatin (17.67%) but not significant (p = 0.138) and less well than pasta (45.66%; p = 0.004) but better than the tea is decreasing (25,86%; p = 0.030). Conclusion: Formula pasta red gedi leaf can be classified standardized herbs that can be used as a complementary alternative medicine cases of dyslipidemia. Formula red gedi leaf tea which is below the standard herbal medicine, research needs with increasing dose and duration of administration.